O receptor atípico de quimiocinas ACKR2 exerce papel protetor na ascaridíase larval por Ascaris suum em modelo murino - Renata Barbosa Peixoto (2017)
Human ascariasis is a highly prevalent geohelmintosis and affects millions of people worldwide and is associated with significant morbidity. This helminthiasis is related to precarious conditions of basic sanitation in addition to reduced socioeconomic conditions. Ascaris sp. infection with presents an acute phase, where the migration of larvae by different organs occurs, and the chronic phase, which occurs after the establishment of adult worms in the small intestine. The information on the aspects of the immune response in the acute phase of the disease is scarce and with this, it becomes important to understand the immunobiological mechanisms in order to propose new tools for the control of ascariasis. Chemokines and their receptors control the migration of cells from the immune system and little is known about their involvement during larval ascariasis. In this study, we demonstrated the participation of the atypical chemokine receptor ACKR2, which degrades CC inflammatory chemokines, in the primo-infection by A. suum. As experimental strategy, deficient mice C57BL/6j in atypical chemokine receptor ACKR2 and their respective wild type were infected with A. suum eggs and, on the eighth day of infection, the parasite load, lung immunopathology, chemokine levels and polarization of the immune response, besides the respiratory parameters were evaluated. The main results suggest the participation of the atypical chemokine receptor ACKR2 in the control of larval migration, or parasitic burden control, by the lungs, besides regulating the pulmonary inflammation generated by this migration. Furthermore, in the primo-infection by A. suum, the atypical chemokine receptor ACKR2 regulates the systemic levels of CC chemokines with a consequent alteration in leukocyte recruitment. Moreover, the atypical chemokine receptor ACKR2 is important in the polarization of the Th2 / Th17 response, related to the control of larval migration in the lungs. It was also verified that the migration of the larvae in animals deficient in the atypical chemokine receptor ACKR2 generated high inflammation and lung injury causing damage in the respiratory function. Taken together, this work suggests that the atypical chemokine receptor ACKR2 chemokine participates in the balance between inflammation and protective immune response, during A. suum larval ascariasis.